Peran Orang Tua dalam Mengembangkan Bahasa Anak Usia Dini Sesuai dengan Tahapan Usianya - Najwa Lubis; Mila Rizky (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
In a child's life, guardians are the primary environment for them to acquire dialect assets additionally from the social environment. The communication that exists between children and guardians is accepted to have a extraordinary impact on dialect advancement in children, where the part of guardians is about how they give incitement to children within the shape of instructing them based on their children's age stages, and teaching children around all things related to dialect improvement. Within the talk of this article, a subjective strategy is utilized. This article points to clarify how the part of guardians in each arrange of dialect development in children is. How guardians take their part in creating children's dialect begins from the primary stages of dialect advancement from birth to one year, one year to two a long time ancient, two a long time to three a long time, three a long time to four a long time, four a long time to five a long time, five a long time to six a long time, and six a long time to seven a long time. It can be concluded that there are numerous parts that guardians can do at each organize of a child's dialect improvement, to be specific welcoming children to talk, perusing stories, welcoming play, presenting objects, welcoming them to open places, tuning in to music, welcoming them to examined stories, appearing pictures and objects around them, telling pixie stories, and introducing the individuals closest to them, tuning in and reacting when the child talks.